2007
DOI: 10.1179/174329307x213873
|View full text |Cite
|
Sign up to set email alerts
|

Local melting and cracking in Al 7075-T6 and Al 2024-T3 friction stir spot welds

Abstract: Local melting of eutectic films and cracking is found in Al 2024 and Al 7075 alloy friction stir spot welds. Dissolution of melted films removes all evidence melted film formation in spot welds made using typical welding parameter settings. For this reason friction stir spot welding is carried out at a rapid plunge rate of 10 mm s 21 and an extremely short dwell time of 0?05 s and after tool retraction, the welded samples are rapidly quenched using a mixture of methanol and liquid nitrogen at a temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
0
38
1
Order By: Relevance
“…[34][35][36] Although it is generally suggested that rotary, friction stir seam and spot welding are solid state welding processes where local melting is precluded, recent research has confirmed that this is not necessarily the case. Local melted film formation has been reported during rotary friction welding of Inconel 718, 37 dissimilar friction stir seam welding of Al alloy and Mg alloy substrates, 38 and during friction stir spot welding of Al alloys 39 and Mg alloys. 40 In AM60/DP600 friction stir spot welds, local melting is associated with the incorporation of zinc into the stir zone.…”
Section: Discussionmentioning
confidence: 98%
“…[34][35][36] Although it is generally suggested that rotary, friction stir seam and spot welding are solid state welding processes where local melting is precluded, recent research has confirmed that this is not necessarily the case. Local melted film formation has been reported during rotary friction welding of Inconel 718, 37 dissimilar friction stir seam welding of Al alloy and Mg alloy substrates, 38 and during friction stir spot welding of Al alloys 39 and Mg alloys. 40 In AM60/DP600 friction stir spot welds, local melting is associated with the incorporation of zinc into the stir zone.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanical properties of thermoplastics decrease with lowering the molecular weight [42]. In FSSW the welding tool produces a compressive pressure in the weld zone [27]. In FSSW of thermoplastics the material in the weld area melts [13].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observations of the FSSW macrostructures, the weld zone of a FSSW joint is schematically illustrated in Figure 2. From the appearance of the weld cross section, two geometrical characteristics of the weld may be identified [27,28]. The first is the thickness of the weld stir zonestir zone (x) which is an indicator of the weld bond area (Figure 2).…”
Section: K Bilicimentioning
confidence: 99%
“…In this connection, the alignment of material in the TMAZ region immediately adjacent to the stir zone extremity is also observed during the tool penetration stage in Al alloy spot welding. 22 As mentioned earlier, tool retraction during friction stir spot welding plastically deforms and displaces material immediately adjacent to the keyhole periphery and tensile straining can promote crack propagation when a melted eutectic film formation produces a line of weakness. With this in mind, the large discontinuities formed close to the extremity of the stir zone (see Fig.…”
Section: Temperature Outputmentioning
confidence: 96%
“…The stir zone temperature decreases since lower sheet material (AZ91) is incorporated into the stir zone during the dwell period in spot welding. 22 The width of the stir zone increases during the dwell period when material from the locations beneath the tool shoulder and from the bottom of the rotating pin is incorporated at the top of the thread and is moved downwards before a and b showing upward displacement of lower sheet material at stage D-2 in Fig. 3 (see arrows): chemical composition at location A is 87?9Mg-11?1Al-1?1Zn (wt-%); c elongation of a-Mg grains and alignment of Mg 17 Al 12 phase (see arrows) in TMAZ region immediately adjacent to stir zone extremity at stage D-2 in Fig.…”
Section: Temperature Outputmentioning
confidence: 97%